Transdermal Drug Delivery System: A Recent Review - V. Sarovar Reddy (Asian Journal of Pharmaceutics (AJP), 2025)
Transdermal medication delivery is the first and foremost delivery of drugs since the inception of treatment for human beings and diseases. In the olden days all the physician focussed on two methods of administering the drugs the first is the oral delivery next is transdermal delivery. The transdermal delivery has even more advantageous than oral dosage forms in some aspects such as overcoming the drug degradation which happens in the entire length of gastro intestinal tract. The removal of formulation is also easy and its application is easy without any other major ingredients. The present review focuses on its origin, anatomy of skin, and its layers concerning the passage of drugs, advantages, disadvantages, applications, physiological properties, biological properties, and limitations, polymers, and various approaches for patches. The major challenge and success in dosage form is the selection of polymers for formulation and its successful drug delivery. This article narrates the majority of evaluation studies to be carried out for the transdermal patches such as Physicochemical evaluation - Thickness, Uniformity of weight, drug content determination, moisture uptake, flatness, folding endurance, Tack properties, tensile strength, Thumb tack test, rolling ball test, quick stick (peel tack) test, in vitro release studies, in vivo studies, percentage water vapor permeation test, human model, swellability, polariscopic examination, stability testing and skin irritation study and their procedure and diagram of experimental performance was presented. The prepared patches need to be successfully evaluated for the above tests and suitable bioavailability must be proved for good market product. The content was also made on present available marketed products and its use such as nicotine patch as Nico dermis to help in smoking cessation, nitroglycerin patches for angina pectoris, estradiol patches in combination with levonorgestrel as climara pro for menopausal symptoms, and some other drugs to cure diseases.